The Character Education in Family Islamic Perspective - Maghfiroh, Lailatul (Yayasan Al-Aziziyah Tlogoagung Kedungadem Bojonegoro, 2024)
AbstractEducation is a human effort to grow and develop physical and spiritual potential in accordance with the character values that exist in society. The character of life that grows is greatly influenced by the surrounding environment, especially the family environment. Every family has a different way of educating children, with the same goal of making children into good and civilized individuals. However, currently there are many phenomena of crime, criminal acts, immoral acts, corruption indicating the low character of citizens in general. Therefore, it is necessary to re-instill character education in families to improve the quality of individuals and society. Character education in the family can be carried out as early as possible slowly through teaching, motivating, modeling, getting used to, and enforcing punishment. The principles of Islamic character in the family that can be instilled are how children develop relationships with parents, relationships with older people, relationships with younger people, relationships with peers, and relationships with the opposite sex. In implementing character education, it must be adapted to the stages of growth and development of children, namely at early age as the formation stage, at adolescence as the development stage, at adulthood as the consolidation stage, and in old age as the wisdom stage.Keywords: Character Education, Family, Islamic Perspective